Mitophagy in Cerebral Ischemia and Ischemia/Reperfusion Injury - Shen, Luoan; Gan, Qinyi; Yang, Youcheng; Reis, Cesar; Zhang, Zheng; Xu, Shanshan; Zhang, Tongyu; Sun, Chengmei (Frontiers in Aging Neuroscience, 2021)
Ischemic stroke is a severe cerebrovascular disease with high mortality and morbidity. In recent years, reperfusion treatments based on thrombolytic and thrombectomy are major managements for ischemic stroke patients, and the recanalization time window has been extended to over 24 h. However, with the extension of the time window, the risk of ischemia/reperfusion (I/R) injury following reperfusion therapy becomes a big challenge for patient outcomes. I/R injury leads to neuronal death due to the imbalance in metabolic supply and demand, which is usually related to mitochondrial dysfunction. Mitophagy is a type of selective autophagy referring to the process of specific autophagic elimination of damaged or dysfunctional mitochondria to prevent the generation of excessive reactive oxygen species (ROS) and the subsequent cell death. Recent advances have implicated the protective role of mitophagy in cerebral ischemia is mainly associated with its neuroprotective effects in I/R injury. This review discusses the involvement of mitochondria dynamics and mitophagy in the pathophysiology of ischemic stroke and I/R injury in particular, focusing on the therapeutic potential of mitophagy regulation and the possibility of using mitophagy-related interventions as an adjunctive approach for neuroprotective time window extension after ischemic stroke.